Your brain on art, nature, and meditation: a pilot neuroimaging study - Krause-Sorio, Beatrix; Becerra, Sergio; Siddarth, Prabha; Simmons, Stacey; Kuhn, Taylor; Lavretsky, Helen (Frontiers in Human Neuroscience, 2025)
ObjectivesExposure to art, nature, or meditation, all transcending human experiences, has beneficial effects on health and wellbeing. Focusing inward or watching art and nature videos elicits positive emotions that can help heal stress-related conditions. In a pilot functional magnetic resonance (fMRI) study, we explored the effect of watching digital art or nature videos compared to contemplating the universal connectedness (also known as transcendental meditation). The instructions were to meditate on the connection to a Universal Soul linked to a sense of expansion and universal connectedness (“one with everything”), which was prompted by a video of the galactic nebula that also controlled for the visual stimuli of the two other conditions.MethodsNine healthy adults (mean age = 29; range = 19–42; 5 women) underwent a block design fMRI scan using a Siemens 3T Prisma scanner. The blocks included (1) nature videos, (2) AI-generated digital art (“machine hallucinations” by Refik Anadol), and (3) videos of NASA Webb-produced images of galactic nebulas. Brain oxygen-level dependent (BOLD) images were processed using FSL Version 6.0 and a general linear model (GLM) tested the contrasts between art, nature, and meditation blocks, using a cluster-corrected p-value of 0.05.ResultsCompared to rest, meditation led to BOLD increases in bilateral lateral occipital and fusiform gyri, as well as right postcentral gyrus and hippocampus. Compared to viewing AI-generated digital art, increased BOLD responses during meditation were observed in left parietal and central operculum, and right pre- and postcentral gyri, and compared to nature, in the left parietal operculum, bilateral postcentral and supramarginal gyri, and bilateral lateral occipital cortices.ConclusionMeditation compared to rest showed brain activation in regions associated with object, sensory, and memory processing. Meditation compared to nature videos led to activity in bilateral sensory and object processing areas, as well as a left sensory integration region (error monitoring), while meditation compared to art showed activity in left sensory integration and right sensorimotor regions. Further studies are needed to delineate the distinct neural signature and therapeutic effects of inner contemplation using human connection to art, nature, or meditative transcendent practices, in the brain and its potential in clinical applications.